Portrait of Keshav Sitaram Thackeray - Ghosh, Ayan (Jio Institute, 2023)
Large framed portraits of prominent Mumbai citizens hang from the upper level of the Corporation Hall. This is Keshav Sitaram Thackeray (1885–1973), father of Balasaheb Thackeray, founder of the political party Shiv Sena. K.S. Thackeray was an author and social activist. He was also one of the key leaders of the Samyukta Maharashtra Samiti that campaigned for the creation of Maharashtra state based on linguistics and for inclusion of Mumbai as the capital of Maharashtra.